Zollinger–Ellison syndrome: modern aspects of diagnostics and treatment - I. V. Mayev; D. N. Andreev; Yu. A. Kucheryavyy; D. T. Dicheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To reflect modern concepts on clinic, diagnostics and treatment of Zollinger–Ellison syndrome (ZES).Key points. ZES is rare disease related to intragastric hyperacidity. Phenomenon of hyperacidity in ZES patients is caused by hypergastrinemia associated with ectopic gastrin production. Disease frequently develops in patients with multiple endocrine neoplasia syndrome of the 1-st type. Clinical presentation of ZES directly reflects hypersecretion of hydrochloric acid with development of erosive — ulcerative lesions of esophagus, stomach and duodenum, resistant to standard dozes of proton pump inhibitors (PPI). One of basic methods of ZES diagnostics is assessment of serum gastrin level and intragastric acid production. Conservative treatment includes prescription of high PPI dozes, and octreotide analogues.Conclusion. ZES is not a common disease, anyhow knowledge of its clinical course is important for duly recognition. ZES should be considered at differential diagnostics in patients with frequently relapsing upper gastro-intestinal erosive-ulcerative lesions and in patients resistant to standard dozes of PPI.